ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN ATAS PENGELOLAAN LIMBAH PADA DINAS KESEHATAN KOTA KUPANG - Nuwa, Yohanes Calvin; Dethan, Minarni Anaci; Oematan, Herly M. (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2023)
This study is entitled "Analysis of the Application of Environmental Accounting for Waste Management in Kupang City Health Office". This study aims to determine the application of environmental accounting at the City of Kupang Health Office, as an effort to reduce the environmental impact caused by the operational activities of the health center and to know the environmental costs of the City of Kupang Health Office. This research is a descriptive qualitative research. The variables used in this study are environmental activities and environmental cost budgets. The results of this study are environmental activities carried out by health centers such as, waste water management using Waste Water Management Installation (IPAL) or infiltration channels that are channeled in the form of septic tank, medical waste using incinerator and non-medical waste in the storage area in a temporary landfill (TPS) and then transported to a landfill (TPA). While the Kupang City Health Office only acts as the management that controls or supervises, monitors or supervises every waste handling activity carried out by the puskesmas. The budget for waste management costs incurred by the Kupang City Health Office from 2017-2020, namely 1) prevention costs such as, third-party service expenditure for medical waste combustion costs and medical waste management training, 2) internal failure costs such as, transport waste management medical and medical junk transport official travel, and 3) environmental detection costs such as medical travel service supervision supervision of medical waste.